Changes in the Functional Potential of the Gut Microbiome Following Probiotic Supplementation during Helicobacter Pylori Treatment. Issue 6 (18th March 2016) - Oh, Bumjo; Kim, Ji Won; Kim, Bong‐Soo
Abstract: Background: Probiotic supplementation is utilized to alleviate the side effects associated with antibiotic therapy for Helicobacter pylori infection. Several studies have described the effects of administration of probiotics on the gut microbiota during antibiotic therapy. However, most of these studies have focused on specific bacteria, thereby providing limited information on the functional roles of the altered microbiota. Therefore, we examined the impact of probiotic supplementation on the structure and functional dynamics of the gut microbiota during H. pylori eradication, using whole‐metagenomic sequence analysis. Methods: Subjects were divided into two groups: the antibiotics group, which received only antibiotics, and the probiotics group, which received antibiotics with probiotic supplementation. The structural and functional profiles of gut microbiota was analyzed using metagenomic DNA extracted from the feces during treatment by Illumina MiSeq system. Results: The overall alterations in microbiota, as revealed by whole metagenome sequencing, were similar with results from our previous 16S rRNA gene‐based analysis. The proportional shift in functional gene families was greater in the antibiotics group than in the probiotics group. In particular, the proportion of genes related to selenocompound metabolism was reduced in the probiotics group, whereas genes associated with the metabolism of nucleotide sugars were increased. Conclusion: The functional alterations of gut microbiota may link to the reduction in intestinal irritation and maintenance of bacterial diversity observed following probiotic supplementation with antibiotic therapy. The potential beneficial roles of altered gut microbiota following probiotic supplementation are expected a reduction in side effects such as intestinal irritation and antibiotics resistance.